Technical Repeatability and Reproducibility of the Stress Radiographs Performed with the Vezzoni-Modified Badertscher Hip Distension Device - Bertal, Mileva; De Rycke, Lieve; Vezzoni, Aldo; Polis, Ingeborgh; Saunders, Jimmy H.; Broeckx, Bart J. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to evaluate the repeatability and reproducibility of the radiographical stress technique using the Vezzoni-modified Badertscher distension device (VMBDD).Materials and Methods Stress radiographs of 10 dogs obtained with the VMBDD were performed consecutively by two different operators and then measured twice by a third veterinarian. The technical repeatability was first assessed individually for the two operators who took the stress radiographs, followed by the technical reproducibility. The obtained variances were used to calculate the 95% limits of agreement for the measurement repeatability, the technical repeatability and the technical reproducibility.Results Both the technical repeatability and reproducibility of the VMBDD technique were good, with the 95% limits of agreement of the measurement repeatability and technical repeatability equalling ± 0.07 overall, and the 95% limits of agreement of the technical reproducibility being ± 0.09.Clinical Significance These results, in combination with the previous results for the measurement of the laxity index, support the use of the VMBDD as a reliable in-house evaluation method to assess the hip joint by trained clinicians. For screening purposes, however, we suggest to limit the number of evaluators, to limit the variability.
Keywords: hip; laxity; radiographs; repeatability; reproducibility